Fuzzy Logic Application to Model Uncertain Route Choice Behaviour of Bus Users in Dhaka City - Basu, Nandita; Mitra, Suman Kumar (Journal of Bangladesh Institute of Planners, 2015)
This paper aims at addressing uncertain human behavior of selecting any particular route based on the predefined road attributes. The study has focused on the route choice behavior of individual road users. This phenomenon of choosing any particular route may depend on number of variables and the influences of variables are different and uncertain on different road users for selecting any route. The study has been conducted on users of five different bus routes of Dhaka City having same origin-destination. Bus users have been asked question regarding the factors that influence each individual’s choice of any particular route. The survey has been conducted for both weekday and weekend. Fuzzy logic approach has been used to model such uncertain behavior and Neuro-fuzzy logic has been used to calibrate the fuzzy logic based model. Results have shown that travel time and waiting time are two most significant factors to influence route choice behavior. Other factors, such as the comfort, safety, security and regularity are also found significantly important. The output results of model have been validated against the surveyed data and it has revealed that Fuzzy Logic model can predict the route choice pattern (route share) to a significant level. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 1-14